Indistinguishable MHz-narrow heralded photon pairs from a whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph (APL Photonics, 2025)
The Hong-Ou-Mandel interference plays a vital role in many quantum optical applications where indistinguishability of two photons is important. Such photon pairs are commonly generated as the signal and idler in the polarization-degenerate spontaneous parametric downconversion (SPDC). To scale this approach to a larger number of photons, we demonstrate how two independent signal photons radiated into different spatial modes can be rendered conditionally indistinguishable by a heralding measurement performed on their respective idlers. We use the SPDC in a whispering gallery resonator, which is already proven to be versatile sources of quantum states. Its extreme conversion efficiency allowed us to perform our measurements with only 50 nW of in-coupled pump power in each propagation direction. The Hong-Ou-Mandel interference of two counterpropagating signal photons manifested itself in the fourfold coincidence rate, where the detection of two idler photons heralds a pair of signal photons with a desired temporal overlap. We achieved the Hong-Ou-Mandel dip contrast of 74% ± 5%. Importantly, the optical bandwidth of all involved photons is of the order of a MHz and is continuously tunable. This, on the one hand, makes it possible to achieve the necessary temporal measurement resolution with standard electronics and, on the other hand, creates a quantum state source compatible with other candidates for qubit implementation, such as optical transitions in solid-state or vaporous systems. We also discuss the possibility of generating photon pairs with similar temporal modes from two different whispering gallery resonators.
CRIS-Team Scopus Importer:2025-05-30

Nonlinear power dependence of the spectral properties of an optical parametric oscillator below threshold in the quantum regime - Shafiee, Golnoush; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schunk, Gerhard; Vogl, Ulrich; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (New Journal of Physics, 2020)
Photon pairs and heralded single photons, obtained from cavity-assisted parametric down conversion (PDC), play an important role in quantum communications and technology. This motivated a thorough study of the spectral and temporal properties of parametric light, both above the optical parametric oscillator (OPO) threshold, where the semiclassical approach is justified, and deeply below it, where the linear cavity approximation is applicable. The pursuit of a higher two-photon emission rate leads into an interesting intermediate regime, between above OPO threshold and very low pump power, where the OPO still operates considerably below the threshold but the nonlinear cavity phenomena cannot be neglected anymore. Here, we investigate this intermediate regime and show that the spectral and temporal properties of the photon pairs, as well as their emission rate, may significantly differ from the widely accepted linear model. The observed phenomena include frequency pulling and broadening in the temporal correlation for the down-converted optical fields. These factors need to be taken into account when devising practical applications of the high-rate cavity-assisted spontaneous PDC sources.
CRIS-Team WoS Importer:2020-08-21

Polarization-entangled photons from a whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Leuchs, Gerd; Marquardt, Christoph (npj Quantum Information, 2024)
Crystalline whispering gallery mode resonators (WGMRs) have been shown to facilitate versatile sources of quantum states that can efficiently interact with atomic systems. These features make WGMRs an efficient platform for quantum information processing. Here, we experimentally show that it is possible to generate polarization entanglement from WGMRs by using an interferometric scheme. Our scheme gives us the flexibility to control the phase of the generated entangled state by changing the relative phase of the interferometer. The S value of Clauser–Horne–Shimony–Holt’s inequality in the system is 2.45 ± 0.07, which violates the inequality by more than six standard deviations.<br
Keywords: Nonlinear optics; Quantum optics

Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Vogl, Ulrich; Dirmeier, Thomas; Shafiee, Golnoush; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald; Gehring, Tobias; Andersen, Ulrik Lund; Leuchs, Gerd; Marquardt, Christoph (Optica, 2019)
Squeezed vacuum states enable optical measurements below the quantum limit and hence are a valuable resource for applications in quantum metrology and also quantum communication. However, most available sources require high pump powers in the milliwatt range and large setups that hinder real-world applications. Furthermore, degenerate operation of such systems presents a challenge. Here, we use a compact crystalline whispering gallery mode resonator made of lithium niobate as a degenerate parametric oscillator. We demonstrate about 1.4 dB noise reduction below the shot-noise level for only 300 mu W of pump power in degenerate single-mode operation. Furthermore, we report a record pump threshold as low as 1.35 mu W. Our results show that the whispering gallery-based approach presents a promising platform for a compact and efficient source for nonclassical light. (c) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-12-06